Desain Konseptual Reaktor Cepat Berpendingin Karbondioksida dan Berbahan Bakar Uranium Alam Dengan Daya 2400 MW - Enda Susanty; Menik Ariani; Idha Royani; Zaki Su'ud; Fiber Monado (Lambung Mangkurat University Press, 2020)
This paper presents the design concept of a carbon dioxide-cooled fast reactor. This reactor utilize U-10%Zr as fuel and SS316 as cladding. The strategy of modified CANDLE (Constant Axial shape of Neutron flux, nuclide densities and power shape During Life of Energy production) was applied for burnup in the core with power 2400 MW. The reactor core calculations were performed with a cylindrical geometry that is varied on the height and diameter of the core using a set of CITATION and PIJ modules on the SRAC (Standard Reactor Analysis Code) program. The ideal core size was obtained with a high of 350 cm, and a diameter of 240 cm with the resulting survey parameter are effective multiplication factor(keff), excess reactivity, radial and axial power distribution, and power peaking. The reactor core reaches a critical condition with keff 1.05 and excess reactivity 5.3% and radial power peaking 1.73. Optimization was done with power flattening, that is by dividing the core into two parts with a fuel fraction of 60% for the inner part with thick of 80 cm and fuel fraction of 65% for the outer part with thick of 40 cm, the results are 1.013, 1.3% and 1.5 for keff, excess reactivity, and radial power peaking, respectively.